1993
DOI: 10.1259/0007-1285-66-788-725
|View full text |Cite
|
Sign up to set email alerts
|

Colonic obstruction following small bowel barium study

Abstract: A case is described in which inspissated barium was retained in the colon for 16 months before causing large bowel obstruction. To our knowledge this is the first case described in which the time interval between barium ingestion and the onset of symptoms was more than a few weeks. Scybalum formation is due to resorption of water from the barium sulphate, which although less common with modern preparations, still appears to be possible in certain high-risk patients. Prolonged retention of barium should be avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In one recent report, a barium meal examination resulted in sigmoid volvulus for which surgical intervention ensued 4 . In one case the colonic obstruction occurred 16 months after barium administration 5 …”
Section: Discussionmentioning
confidence: 99%
“…In one recent report, a barium meal examination resulted in sigmoid volvulus for which surgical intervention ensued 4 . In one case the colonic obstruction occurred 16 months after barium administration 5 …”
Section: Discussionmentioning
confidence: 99%
“…In this review 24 articles [7–30] describing 34 cases were initially identified. However two articles were excluded; one described two cases in which a barium examination had converted a partial obstruction to a complete obstruction and therefore did not represent barolith‐induced obstruction as such [10].…”
Section: Literature Searchmentioning
confidence: 99%
“…The latter could not be included in this review because no specific details of the case were given. Details of the remaining 31 cases reported in 22 articles [7][8][9][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] are summarized in Appendix 1.…”
Section: Literature Searchmentioning
confidence: 99%